Anger and its management: an overview - Dr. Magesh Rajagopal (Tamil Psychiatry Journal, 2025)
Anger as an emotion is naturally felt by all humans. However, if this anger turns into resentment and affects oneself and others, it becomes a problem. Reasonable anger ensures one’s rights and security. However, excessive anger can greatly affect one’s mind and body and can also affect relationships. Anger is one of the five basic human emotions. Sometimes, anger is an expression of our impulses. Although we cannot completely avoid anger, we can easily manage it. Many of us have the idea that the consequences of anger are always negative and always try to suppress it. But as a result of suppressing it, one day the suppressed anger multiplies and manifests itself in an undesirable way, affecting others and ourselves. But when anger is handled properly, some constructive results also occur. This article discusses in detail the negative consequences of excessive anger and the importance of anger management. The relationship between alcohol consumption and increased anger in alcoholics is discussed here. Various research based evidence on practical strategies of anger management is also discussed here.